Harapan dan Identitas Etnis pada Remaja Nusa Tenggara Timur - Panis, Marleny Purnamasary (Jurnal Online Psikogenesis, 2023)
The formation of ethnic identity illustrates the important task for emotional development during adolescence. Hope is a protective factor for adolescents during the process of identity formation. This study aims to determine the effect of hope on the development of ethnic identity of adolescents in NTT. The participants of this study were 45 adolescents aged 17-19 years old who were studying at several universities in NTT. The sample of the study was taken by using purposive sampling technique. This study used the Children Hope Scale (CHS) and Ethnic Identity Scale to measure the effect of hope on the development of ethnic identity of adolescents in NTT. Hypothesis testing using simple linear regression analysis resulted in significance value (Sig.) 0.040 <0.05, t-statistic 2,115> 2,015, R square = 0.094. The results of the study show that there is a significant effect of hope variable amounts to 9,4% on the development of ethnic identity of adolescents in NTT. This study implies the need to cultivate hope as an effective variable in developing emotional skills of adolescents by way of improving solidarity among members in various ethnic groups in NTT.